Modelling the bird flight : Scientific Report 2007-2010 - Ruck, SebastianOertel, Herbert (KIT Scientific Publishing, 2011)
The aerodynamics of flying birds and insects plays a crucial role in the domain of aeronautical engineering. The energy-efficient construction of winglets for airplanes, the formation flight of tactical aircraft or the drone engineering or military applications are inspired by birds. This holds also for flow and structure simulation of flapping wing motion, taking the unsteady aerodynamics and corresponding wing deformations into account at high flow velocities and flapping frequencies.